Integrating Moderation within the Immoderate-Labelled Islamic Movement (A Case Study of the Personal Experience and Al-Guroba Da'wah Initiatives) - Marheni, Cut Linda; Zumadil, Zumadil (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2025)
This research investigates the dynamics of Islamic movements in the setting of religious understanding in Central Aceh, Indonesia. This is carried out by a case investigation, based on the private experiences of an individual and the establishment and the growth of the Al-Guroba dakwah initiative headquarters. By doing an in-depht interview, we examined the evolution in the religious understanding of a figure exposed to various religious histories; from traditional institutions, Salafism, to a more moderate religious thought. This study underscores how trans-national support; ideologically and financially, contributes to the dissemination of fundamentalist Salafism, which often leads to